Chemical characterization and biological valorisation of propolis extracts - (:unkn) unknown (My University, 2014)
Propolis is a resinous substance collected by honeybees from various plant sources. Its secondary metabolites composition depends on the local flora around the collection site. During this study, the chemical characterization of a representative sample of a French propolis produced by ‘‘Ballot-Flurin Apiculteurs’’ led, through structural identifications involving HPLC/DAD/MS as well as 1D & 2D NMR, to the identification of 51 compounds, two of them being new. Phenolic acids and esters and flavonoids identified in this propolis indicate that it belongs to the so-called "poplar" type. The evaluation of the biological activities of different extracts or isolated compounds showed that this propolis, which exhibits a significant antioxidant activity (DPPH and ORAC) associated with a very interesting anti-glycation (anti-AGEs) potential, would represent a good candidate for the prevention of diseases involving AGEs such as diabetes. These extracts or compounds also exhibit antifungal and antibacterial activities towards two Candida yeasts on the one hand, and Staphylococcus aureus and its methicillin-resistant and susceptible strains on the other hand, the latter being nowadays responsible for many nosocomial infections. A study dealing with the inter-batch variability accompanied by an optimization of the industrial extraction process using experimental design were also carried out (Confidential part). Finally, the analysis of three propolis originating from Latin America (Mexico) and Africa (Ivory Coast and Uganda), revealed a great diversity of results in relation to chemical compositions and biological activities.
Keywords: African Research